2020
DOI: 10.1111/jcmm.15633
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 attenuates the inflammatory process in mouse model of LPS‐induced keratitis

Abstract: Keratitis is an ocular inflammatory disease characterized by corneal derangement, due to alterations of structural components such as tight junctions and infiltration of leucocytes into the cornea. These result in stromal keratitis, corneal thinning, and ultimately corneal perforation and scarring. Early neutrophil infiltration into the cornea causes local inflammation that greatly contributes to the host tissue destruction through the release of proteolytic enzymes and inflammatory mediators, ultimately leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Intrastromal injection of 2 μg of Lipopolysaccharide (LPS, Sigma) from Pseudomonas aeruginosa, dissolved in 2 μL of phosphate-buffered saline (PBS, Sigma), was performed in both the eyes of male CD-1 mice under direct microscopic observation, according to previous studies [ 23 , 24 , 25 ]. Briefly, CD-1 mice were anaesthetized by pentobarbital (45 mg/kg in saline, i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrastromal injection of 2 μg of Lipopolysaccharide (LPS, Sigma) from Pseudomonas aeruginosa, dissolved in 2 μL of phosphate-buffered saline (PBS, Sigma), was performed in both the eyes of male CD-1 mice under direct microscopic observation, according to previous studies [ 23 , 24 , 25 ]. Briefly, CD-1 mice were anaesthetized by pentobarbital (45 mg/kg in saline, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…An investigator unaware of the treatments evaluated the development of keratitis by using a biomicroscope. As previously described [ 24 , 27 ], keratitis was scored as follows: 0 = normal, clear cornea, no inflammatory reaction; 1 = mild corneal haze with visible iris; 2 = moderate corneal flare with moderate corneal haze and superficial punctate keratitis; 3 = significant corneal opacity, infiltration of cells in the stroma; and 4 = damage and loss of corneal tissue. Positive keratitis was scored as >1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these previous results, our data increased Ki67 expression in the control group; however, such increase was reversed by SA treatment. 35, 36 (Figure 5). LPS is well known as a proven NLRP3 inflammasome activator.…”
Section: Discussionmentioning
confidence: 99%
“…Bathina and Das found that RvD1 can prevent streptozotocin-induced type 1 diabetes by reducing oxidative stress and suppressing inflammation [ 10 ]. In mouse model of lipopolysaccharide-induced keratitis, RvD1 was reported to ameliorate the inflammatory process [ 11 ]. In addition, PD1 was also found to enhance resolution of inflammation in lipopolysaccharide-induced acute lung injury [ 12 ].…”
Section: Introductionmentioning
confidence: 99%